The Process of Organizing and Developing Pesantren (Islamic Boarding Schools) Into Modern Institutions: A Multi-Cases Study in Indonesia - Jalil, Abdul; Imron, Ali; Arifin, Imron; ., Maisyaroh (International Journal of Membrane Science and Technology, 2023)
This study reviews and examines how Pesantren (Islamic Boarding Schools) exist, starting from the process of organizing, developing, what obstacles are found, up to what strategy is used by the pesantren to develop and maintain its existence. A qualitative approach was used in this study. Data collection from the multiple case studies was through observation, interview and document study. data was analyzed through a reduction process by analyzing each individual case then also analyzed across cases in a cross-case analysis. The data was also checked for validity, reliability and objectivity to ascertain the degree of credibility, dependability and conformability. The cross-case findings show that pesantren after establishment go through phases that involve the initial process of searching for identity to efforts to maintain existence through a formulated support system. Pesantrens have a unique organizational culture in various aspects and parts and are not the same as other organizational cultures. The process of organizing pesantrens indicated dynamism in the organizational process while adapting more formal administrative and procedural approaches that conform with contemporary organization management models. It was also found that the challenges of pesantren are more from internal factors especially relating to resistance to change and development emanating from the mindset of the leadership. The study reveals the spiritual framework of the founders of pesantrens in pioneering, organizing and developing their institutions. The novelty of this study lies in its comprehensive examination of pesantren starting from the process of organizing, developing and the strategies used during the development process how they exist, obstacles faced up to the strategies they use to develop and maintain their existence. The changing environment has compelled pesantren continue to improve and move minds to grow initiatives to keep up with the changes. and incorporate conventional elements into the implementation of their education system as they face a dilemma between changing or dying under pressure from the power of change itself.